Formazione etica ed emozioni Prospettive di virtue ethics neo-aristotelica - NICCOLI, ARIELE (Premio Ricerca «Città di Firenze», 2020)
Affectivity - especially the emotions - are proved to be a key-point of ethical formation. This book aims at clarifying which thesis the neo-aristotelian Virtue Ethics hold about emotion education, by integrating philosophy of education, philosophy of emotions and moral epistemology. Virtue Ethics, compared to deontology and utilitarianism-consequentialism, offers the more appropriate framework to conceive the relations between education, emotions and ethics. The volume discusses cognitive-evaluative theories of emotions and address the anti-rationalist challenge, based on empirical evidence about how emotions impact on moral judgments. Anti-rationalism, it is argued, is incompatible with the purpose of shaping the emotions looking at our best moral reasons. Then, two Aristotelian educational theses are put forward: all the emotional dispositions - both 'positive' and 'negative' - should be cultivated, and all the emotional dispositions admit an appropriate moral form.